A spelling corrector for Basque based on morphology. - Aduriz, I; Urkia, M; Alegria, I; Artola, X; Ezeiza, N; Sarasola, K (Literary & Linguistic Computing, 1997)
This paper describes the components used in the elaboration of the commercial Xuxen spelling checker/corrector for Basque. Because Basque is a highly inflected and agglutinative language, the spelling checker/corrector has been conceived as a by-product of a general purpose morphological analyser/generator. The spelling checker/corrector performs morphological decomposition in order to check misspellings and, to correct them, uses a new strategy which combines the use of an additional two-level morphological subsystem for orthographic errors, and the recognition of correct morphemes inside the world-form during the generation of proposals for typographical errors. Due to a late process of standardization of Basque, Xuxen is intended as a useful tool for standardization purposes of present day written Basque.